Mycobacterium Chelonae associated with rapid erosion of non-sutured laparoscopic gastric band. (2016) - Memon, Muhammed Ashraf; Memon, Breda; Whitby, Michael
Highlights: Mycobacterium chelonae is found throughout the environment e.g. sewage and tap water. M. chelonae and M. abscessus are considered the most drug resistant of the NTM group. Consider environmentally acquired infection with rapid erosion of gastric band. Abstract: Introduction: To describe a case of rapidly eroded laparoscopic placed non-sutured gastric band secondary to Mycobacterium chelonae . Presentation of case: A 65 year old male, who had undergone laparoscopic gastric banding two months prior for morbid obesity, presented to the clinic complaining of abdominal pain and night time fever of 4 days duration. Urgent gastroscopy revealed eroded gastric band which was removed laparoscopically. Discussion: M. chelonae are not uncommon in Queensland. Although the mode of acquisition of infection remains unclear, it is suspected that human disease results from environmental exposure to dirty soil and water. The patient lives in rural Queensland and uses tank water which may be contaminated with M. chelonae . Conclusion: It is imperative to consider environmentally acquired infection in patients with rapid erosion of non-sutured gastric band.